Botrytis cinerea in raspberry in Serbia II: Growth rate and virulence of isolates - Tanović, Brankica Borko; Hrustić, Jovana; Mihajlović, Milica; Grahovac, Mila; Delibašić, Goran (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2015)
Growth rate and virulence of 130 isolates of Botrytis cinerea, derived from raspberry fruitoriginating from six commercial fields in a raspberry growing region of Serbia and classified in two morphological and four genetic groups were studied. The results showed significant differences in mycelial growth rate among the isolates. The highest and lowest recorded growth rates were 24.5 mm/day and 8.4 mm/day, respectively, while the growth rate of most isolates ranged from 15.8 to 21.8 mm/day. The growth rate of isolates that belong to different morphological and genetic subgroups varied similarly. Furthermore, growth rate intervals of all subgroups overlapped, suggesting that the groups cannot be distinguished based on growth rates of the isolates contained. The studied B. cinerea isolates exibited different levels of virulence towards vine, sunflower and raspberry leaves, while an analysis of variance revealed that both the isolates and the inoculated host species were significant sources of variation (P
Keywords: Botrytis cinerea; Raspberries; Serbia